Reflection through critical friendship: Promoting growth of teachers - Kelley, Michaelann; Curtis, Gayle A.; Craig, Cheryl J.; Reid, Donna; Easley, Annette (Frontiers in Education, 2022)
Abstract: This article draws on the longstanding collaborative work of the Portfolio Group (a cross-school, cross-institution teacher/teacher educator/researcher group) to explore the role of collaborative critical friendship in our group’s reflective practice and the influence on our individual growth as teachers/teacher educators/researchers. Employing narrative methods and aided by a conceptual frame of reflection, critical friendship, and optimal experience, this article highlights how teacher practice is enhanced and strengthened when teachers come together as critical friends to share stories of experience, to examine experiential currents, undercurrents, and riptides (i.e., plotlines, dilemmas, contexts, interactions, politics, etc.), and to provide meaningful feedback that supports colleagues’ professional growth.